Gas Mass Spectrometry of Industrial Yogurts - Vladimir S. Sibirtsev; Alexey G. Kuzmin; Yuri A. Titov; Anna Yu. Zaitseva; Vladislav V. Sherstnev (Техника и технология пищевых производств)
Food safety and quality are especially important in the dairy industry. Mass spectrometry is an effective tool of state control in this sphere. The research objective was to study the prospects for gas mass spectrometry with smart mathematical processing in assessing the composition and quality of dairy products. The study featured 11 samples of fresh and acidified yoghurts from different manufacturers and with various starters, functional food additives, etc. These samples and their packaging were evaluated using a small-sized quadrupole gas mass spectrometer MS7-200 with electron impact ionization developed at the Institute for Analytical Instrumentation, Russian Academy of Sciences. The data obtained were mathematically processed by the method of principal components. Based on the ratios of peak intensities at m/z = 55, 56, 57, 58, 59, 60, 61, 64, 67, 69, 70, 71, 72, 73, 74, 84, 85, and 88 Da, the fresh and expired samples were classified not only by the degree of freshness, but also by the composition and quality of the microbiological starters, raw materials, food additives, etc. In addition, some packaging materials proved to be of poor quality. In this study, the method of gas mass spectrometry was supplemented by the authentic methods for selecting gas emissions from yoghurts and packaging, accelerated acidification, and smart mathematical processing. The approach proved to be time-saving, sensitive, selective, available, and cost-effective. As a result, it demonstrated good potential as a means to control the composition and quality of dairy products and their packaging.